Comprehensive Design Approach for Field-Oriented Control of Interior Permanent Magnet Synchronous Machines - Busarello, Tiago Davi Curi; Bubshait, Abdullah; Varaprasad, Oruganti V. S. R.; Alsaleem, Abdulhakeem; Simões, Marcelo G. (IEEE, 2022)
This paper presents a comprehensive design approach for a field-oriented control of Interior Permanent Magnet Synchronous Machines (IPMSM). Initially, the IPMSM model is revisited. Later, a step-by-step procedure for designing a Field Oriented Control (FOC) Strategy for IPMSM is presented. The control strategy is in dq-rotating reference frame and it is synchronized with the rotor position. The current controllers are designed based on setting a desired closed-loop time-constant while the speed controller is designed based on a frequency response approach, which is different from the conventional methods. The proposed approach supplies all the steps to accurately tuning the parameters of the Proportional-Integrator (PI) controllers of the current and speed control loops. Furthermore, the proposed design approach is a fast, reliable and accurate guide to implement IPMSM drive based on FOC. Results from a Hardware-in-Loop (HIL) with external microcontroller are presented. The comprehensive design approach is verified under two different IPMSM parameters and the results showed its effectiveness.
Keywords: hardware-in-the-loop simulation; machine vector control; permanent magnet machines; Variable speed drives; electric machines; fi=Sähkötekniikka|en=Electrical Engineering|